2010
DOI: 10.4172/1948-5948.1000022
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Physico-Chemical and Nutritional Parameters for the Production of Ethanol from Mahua Flower (Madhuca indica) Using Saccharomyces Cerevisiae ? 3090 Through Submerged Fermentation (smf)

Abstract: Effect of various Physico-Chemical and Nutritional parameter for the production of ethanol from mahua flower using Saccharomyces cerevisiae -3090 through submerged fermentation have been studied. Substrate mahua flower contains 68% Total sugar. Yeast strain S.cerevisiae-3090 was obtained from National Collection of Industrial Microorganisms (NCIM), Pune, South India. Maximum production of ethanol obtained at different optimized parameters such as substrate concentration at 28%, p H at 5.0, Inoculum level at 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…These results indicate that yeast cells easily utilized various nitrogen sources to metabolize nitrogenous substances for their growth and other metabolic activities. A similar trend towards an increase in the yield of ethanol by S. cerevisiae 3090 in the presence of nitrogen sources has also been reported in another investigation (Benerji et al 2010).…”
Section: Resultssupporting
confidence: 65%
“…These results indicate that yeast cells easily utilized various nitrogen sources to metabolize nitrogenous substances for their growth and other metabolic activities. A similar trend towards an increase in the yield of ethanol by S. cerevisiae 3090 in the presence of nitrogen sources has also been reported in another investigation (Benerji et al 2010).…”
Section: Resultssupporting
confidence: 65%
“…This could be due to the inhibitory activity of the nitrogen sources. Benerji et al (2010) reported higher ethanol production (13.29%, w/v) in the presence of urea (0.06 %) from mahula flower by using S. cerevisiae. In another study, Laopaiboon et al (2009) reported higher ethanol production (120.68 ± 0.54 g/ l) in the presence of peptone (5g/l) and yeast extract (3g/l) in sweet sorghum juice.…”
Section: Effect Of Different Nitrogen Sourcesmentioning
confidence: 99%
“…Alshiyab et al (2009) reported that by using bigger reactor size, the effect of gaseous products in fermentation medium was reduced and enhanced both bacterial productivity and biomass concentration, where Brethauer and Wyman (2010) reported that some continuous fermentations are now employed for commercial ethanol production from cane sugar and corn to take advantage of higher volumetric productivity, reduced labor costs, and reduced vessel down time for cleaning and filling.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol was determined by the oxidation method (Benerji et al, 2010). Fermentation efficiency (%) was determined as (Sedha et al, 1984):…”
Section: Analysis Of Culture Beermentioning
confidence: 99%